Catheter Associated Urinary Tract Infection Based on Surveillance Attributes in RSU Haji Surabaya - Spica Redina Vebrilian (Universitas Airlangga, 2016)
The surveillance system is very instrumental in reducing the incidence of nosocomial infections, so the nosocomial infection surveillance system needs to be implemented in hospitals. Catheter-associated Urinary Tract Infection (CAUTI) surveillance is one of the program's focuses on infection prevention and control efforts at the Haji Public Hospital (RSU Haji) Surabaya in 2015. The success of a surveillance system is highly dependent on the interrelation of the attributes contained therein. In 2015, there was a delay in the collection of reports exceeding the specified deadline and there were also columns in the confirmation sheet that were not filled. This study aims to evaluate CAUTI surveillance based on surveillance attributes at the RSU Haji Surabaya in 2015. This study is an evaluative descriptive study. The variables studied were CAUTI surveillance attributes at RSU Haji Surabaya, namely simplicity, flexibility, acceptability, sensitivity, positive predictive value, representativeness, timeliness, data quality, and stability, while the research respondents were Infection Control Nurse (ICNs), Infection Control Link Nurses (ICLN), and the head of the room. Data collection techniques carried out by interview and documentation study. The results showed that the surveillance attributes were simple, had high acceptability, high sensitivity, high positive predictive value, representative, and high stability. However, other attributes are inflexible, not timely, and have low data quality. Alternative solutions that can be done are improving supervisory functions in each unit, establishing hospital data standardization, setting reward, and punishment systems.